The Interpreter : a novel - Robinson, Brooke (Playwright) (Harper, 2023)
"Innocent or guilty: it all hinges on a single word . . .Thanks to a nomadic childhood, Revelle Lee is fluent in ten languages, which she puts to use at crime scenes and in courtrooms across London. Being a court interpreter is a stressful job, one that makes her privy to the most personal and often dark details of others' lives. In the meantime, she's close to adopting a six-year-old boy named Elliot from foster care. Revelle is determined to be the mother she never had, and to make up for a terrible mistake she made years ago. Though the sweet, loving little boy is learning to trust her, she's begun receiving disturbing messages which she suspects are from his birth family. When one of her cases involves a murder victim she knew slightly, Revelle fears she's seeing a miscarriage of justice play out. Putting both the adoption and her career at risk, she deliberately mistranslates a Polish man's alibi to put his accused friend behind bars, even though he insists he's innocent. Revelle thinks she's gotten away with it free and clear. But someone seems to know what she's done--and about her long-ago error and its terrible consequences. And they intend to destroy Revelle's life, piece by piece. . ." --